2013
DOI: 10.4236/ojst.2013.38069
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain fracture of metal-ceramic tooth-supported and implant-supported restorations: A review

Abstract: Metal-ceramic restorations are widely used in dentistry with a high degree of general success. However, fracture of these restorations does occur and usually frustrates both the dentist and the patient. Objective: This literature review discusses the factors that may lead to the fracture of these restorations whether they are tooth-supported or implant-supported with the aim of making dentists and technicians aware of these factors to avoid them. Factors reviewed include: technical factors, dentist-related fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…(7,10) Misfiting implant cemented restorations can lead to biomechanical failure, components fracture or even bone loss. (2,16) Studies evaluating the marginal adaptation of fixed restorations on teeth or implants suggest different methods of measuring marginal discrepancy between the restoration margins and abutment tooth or implant abutment. Of these, the direct microscopic, sectioning and replica methods were mostly preferred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(7,10) Misfiting implant cemented restorations can lead to biomechanical failure, components fracture or even bone loss. (2,16) Studies evaluating the marginal adaptation of fixed restorations on teeth or implants suggest different methods of measuring marginal discrepancy between the restoration margins and abutment tooth or implant abutment. Of these, the direct microscopic, sectioning and replica methods were mostly preferred.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Although most of the concentration today is on allceramic restorations, metal ceramic restorations, whether they are tooth supported or implant supported, are still considered as the gold standard because of their excellent biocompatibility, consistent esthetics,superior strength and marginal adaptation. (2) The production of the metallic framework in the dental laboratory has been carried out using the lost wax casting technique. (3) Although the alloys of choice were gold-based when the casting technique was first developed, they were gradually replaced by base-metal alloys such as nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an access hole to the screw in the occlusal surface of screwed restorations significantly reduces ceramic resistance to fractures, as the head of the screw or the restorative composite material with which part of the hole is covered occupies from 50% to 66% of intercuspal distance. 20 In other words, there is still a minimum width of ceramics around the opening access to the screw that increases the chances of fracture. In addition, the remaining hole indicates the interruption of structural continuity of ceramics, leading to changes on its center positioning through which the material choses during the sintering process.…”
Section: Summary Of the Findingsmentioning
confidence: 99%
“…Recently, Kaleli et al [22] demonstrated that Co-Cr dental alloy fabricated via SLM had significantly higher bond strength than cast alloy. In metal-ceramic restorations, another frequent reason for porcelain fracture is the lack of rigidity and the distortion of the metal substructure [23]. Therefore, mechanical anisotropy should also be taken into consideration when a metal substructure for a metal-ceramic restoration is built.…”
mentioning
confidence: 99%